2013
DOI: 10.1902/jop.2012.120436
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Periodontal Disease of Individuals With and Without HIV Undergoing Highly Active Antiretroviral Therapy

Abstract: Individuals with HIV undergoing HAART, compared with individuals without HIV, had no statistically significant differences in mast cell densities in gingival tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Mast cells are involved in many pathological conditions such as asthma, gingivitis, periodontitis, and oral lichen planus with their numbers and MMPs expression significantly increased in chronic periodontitis. [ 10 ] Thus, mast cell analysis can serve as a useful histological marker for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are involved in many pathological conditions such as asthma, gingivitis, periodontitis, and oral lichen planus with their numbers and MMPs expression significantly increased in chronic periodontitis. [ 10 ] Thus, mast cell analysis can serve as a useful histological marker for periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior analysis of our research group 17 , the results did not demonstrate a statistically significant difference in the mast cell densities in HIV-infected individuals with periodontal disease undergoing HAART in comparison with non-HIV-infected individuals with periodontal disease. It was suggested that this fact may well be the result of the application of HAART in individuals with HIV 17 . Considering the importance of the mast cell in the immune response, it was evaluated the hypothesis of an alteration on the mast cell degranulation in gingival tissue of HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%